A Comparative Study of Tractors with Special Reference to Sonalika Tractor - Rajput, Uday Singh; Tyagi, Mohit (Indian Journal of Marketing, 2008)
India is the largest manufacture of tractors in the world. The growth has been continuous and good for several years. In the current year, sales have declined by a good 12 per cent in the first six months. With new entrants fighting for market share, competition is intense. There is a welcome focus on R&D directed towards greater fuel efficiency and longer life. Decades of oligopoly and cartelization may, hopefully, give way to competitive market-orientation that would provide some consumer delight. The tractor industry in India has developed over the years to become one of the largest tractor markets in the world. From 50,000 units in the early eighties, the size of the tractor market in the country has grown upto over 200,000 units. Today the industry comprises of 14 players, including three MNCs. The opportunities still are huge considering the low farm mechanization levels in the country. After a downturn during the last three to four years, the industry is back on a growth path, which we believe would sustain in coming years as well. During the fiscal 2003-04, the industry volumes as a whole reached 1,89,000 units, the first growth year since 1999-2000. The trend continued in the first half of fiscal 2004-05 as well. Tractor sales during this period have grown by 45 per cent to 1,11,000 units against 76,000 units in the corresponding period of last year. During the period 1998-2000, tractor manufacturers had build up large inventory levels at the dealer's end, in the race for cornering greater market share.